2012
DOI: 10.1007/s00030-012-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

Regular and irregular solutions for a class of elliptic systems in the critical dimension

Abstract: Abstract.We study regularity properties of weak solutions in the Sobolev space W 1,n 0 to inhomogeneous elliptic systems under a natural growth condition and on bounded Lipschitz domains in R n , i. e. we investigate weak solutions in the limiting situation of the Sobolev embedding. Several counterexamples of irregular solutions are constructed in cases, where additional structure conditions might have led to regularity. Among others we present both bounded irregular and unbounded weak solutions to elliptic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Moreover, for general elliptic systems which need not be derived from an Euler system and for which u is not a minimizer to (1.3), it is known by a counterexample of Struwe [39] that (1.13) does not imply Hölder continuity of bounded W 1;2 solutions if f has quadratic growth in ru. For further counterexamples to this subject see [1]. On the other hand it is shown in [42] that the so-called angle condition, which is a refinement of (1.13) implies the Hölder continuity of a weak solution.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 95%
“…Moreover, for general elliptic systems which need not be derived from an Euler system and for which u is not a minimizer to (1.3), it is known by a counterexample of Struwe [39] that (1.13) does not imply Hölder continuity of bounded W 1;2 solutions if f has quadratic growth in ru. For further counterexamples to this subject see [1]. On the other hand it is shown in [42] that the so-called angle condition, which is a refinement of (1.13) implies the Hölder continuity of a weak solution.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 95%
“…Beck and Frehse [1,Thm. 1.4] demonstrated that, under zero-Dirchlet boundary conditions, there is at least one weak vector-valued solution u : Ω → R N that is locally Hölder continuous in the critical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Let Ω ⊂ R n , n ≥ 2 be a bounded, Lipschitz domain. Beck and Frehse [1] considered elliptic systems of the type: div (a(x, u, Du)) = a 0 (x, u, Du) in Ω ⊂ R n .…”
Section: Introductionmentioning
confidence: 99%
“…In this connection remark that (1.1) is a nonlinear degenerate elliptic system with critical growth nonlinearity H(u)J u on the right-hand side that is merely integrable for maps u of class W 1,n . It is well-known that such systems in general admit very singular solutions and that a general regularity theory is only possible provided the right-hand side nonlinearity has a special structure (see for instance [1]). As mentioned, this is fully exploited for the system in two dimensions n = 2 by Rivière's result, and the hope is that the structure of H(u)J u remains strong enough to ensure regularity also for n ≥ 3, at least when backed up by appropriate additional hypotheses on H. We mention the results of Mou and Yang [20] who proved that solutions of (1.1) are C 1 , provided that either H is constant or u is weakly conformal.…”
Section: Introductionmentioning
confidence: 99%